Intra and extra - Bokov, Andrey (project baikal, 2024)
The subject of the article is the dialectics of cultural space and living environment as a combination of activity and place. The author introduces the concepts of ‘intra’ and ‘extra’ as complexes with different internal structure and relation to the environment. ‘Intra’ (closed) and ‘extra’ (open) mutually define each other and present the essence through conflicts, dispute and dialogue. The relationship of boundaries and roads is the result of different strategies and different views on the space. The ontological predisposition to openness and closedness of cultural spaces characterizes different stages of the civilizational path, different organization levels and different architecture.
Keywords: cultural space; ‘intra’ and ‘extra’; open and closed; boundaries; communication; hierarchy; architecture